Physicochemical studies of liquid pollutants using reversed flow gas chromatographic techniques - Khalisanni, Khalid (2011)
Evaporation of pollutant liquid is a vital ecological fate when the compounds are introduced into both freshwater and marine environments through industrial effluents, or introduced directly into the air from industrial unit processes such as bioreactors and cooling towers. In such cases, reversed-flow gas chromatography (RF-GC) method is needed to measure the physicochemical properties of the pollutant liquids. RF-GC sampling technique is an effortless, fast and accurate procedure. Since the earliest publication on RF-GC, the method has been used to study physicochemical quantities by measuring the value of one in the presence of another. The application of the method embraces the area of environmental sciences, food chemistry, chemical kinetics, catalyst and catalysis. In the present work, RF-GC was used to measure the diffusion coefficient of vapors from liquid into a carrier gas and at the same time to determine the rate coefficient for the evaporation of the respective liquid. The mathematical expression describing the elution curves of the samples peaks was derived and used to calculate the physicochemical parameters for the selected liquid pollutants such as, methanol, ethanol, 1-propanol, 1-butanol, n-pentane, n-hexane, n-heptane and n-hexadecane evaporating into the carrier gas, nitrogen. The values of diffusion coefficients found were compared with those calculated theoretically or reported in the literature, and the values of evaporation rate were used to determine the activation energy of respective samples using Arrhenius equation. An interesting finding of this work is, by using an alternative mathematical analysis based on equilibrium at the liquid-gas interphase, the comparison leads to profound agreement between the theoretical values of diffusion coefficients with the experimental values.